2017
DOI: 10.5114/biolsport.2017.64584
|View full text |Cite
|
Sign up to set email alerts
|

Reticulocyte and erythrocyte hypochromia markers in detection of iron deficiency in adolescent female athletes

Abstract: The aim of this study was to analyse the effectiveness of new haematology parameters related to reticulocytes and mature red blood cells to differentiate pre latent and latent iron deficiency. The study included 219 female athletes (aged 15-20 years) representing volleyball, handball, cycling, canoeing, cross-country skiing, swimming and judo. To assess iron status the concentration of ferritin, soluble transferrin receptor (sTfR), iron and total iron binding capacity (TIBC) were determined in serum. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…The high frequency of both iron and vitamin D deficiencies observed in the present study are in accordance with many earlier studies concerning physically active subjects [ 10 , 12 , 19 , 21 , 22 , 27 , 43 ]. This confirms that the problem regarding deficiencies in both nutrients in athletes is still present.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The high frequency of both iron and vitamin D deficiencies observed in the present study are in accordance with many earlier studies concerning physically active subjects [ 10 , 12 , 19 , 21 , 22 , 27 , 43 ]. This confirms that the problem regarding deficiencies in both nutrients in athletes is still present.…”
Section: Discussionsupporting
confidence: 93%
“…The groups particularly exposed to deficiencies of this mineral are women of reproductive age, children and adolescents [ 2 , 16 , 17 ]. Results from many studies indicate that athletes are also at high risk for iron deficiency [ 18 , 19 , 20 ], and this applies especially to physically active women [ 19 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Recently, different reticulocyte parameters are being studied in the diagnosis of IDA in various age groups but their analysis exclusively in pregnancy is rarely reported. 6,7 The major advantage of these reticulocyte parameters is that it can be evaluated easily with recent automated hematology analyzers using routine blood samples. The feasibility and the ease of use of reticulocyte parameters may also prove beneficial in evaluation of IDA in pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Since rigorous physical exercise may also stimulate inflammation [1,4], this parameter could add value in diagnosing iron status in athletic populations. To date, few studies have examined the utility of CHr as an assessment tool in sport [25,26,27]. The most commonly accepted CHr cut-off value for anemia is 28 pg [12,13,20], but no standardized threshold exists that would allow a robust diagnosis of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…Because reticulocyte parameters exhibit only minor changes under physical training [26], other indices of maturing red blood cells could have diagnostic utility in sport. Our recent study demonstrated visible changes in many reticulocyte indices among female athletes already at a very early stage of ID [25]. Furthermore, other novel indicators of mature red blood cells are emerging as reliable tests for detecting ID before overt anemia is present, in both athletic [25,26] and non-athletic cohorts [19,23], although their reference intervals have not been established.…”
Section: Introductionmentioning
confidence: 99%